THE CHANGE OF FUNCTION AND MANAGEMENT OF SITI HINGGIL KASUNANAN PALACE SURAKARTA AS A TOURISM COMMODITY - BRM. Suryo Triono; Cahyani Tunggal Sari (Proceeding IICACS, 2019)
North Siti Hinggil Kasunanan Palace Surakarta is part of Kasunanan Palace Surakarta building is used by citizen of Kraton for formal occasion of the kingdom, such as punggawa or high officials facing the king (nangkil) ceremony, Sekaten ceremony, Mahesa Lawung and the coronation ceremony of the king. The selection of Siti Hinggil as the object of this study considers the important role of Siti Hinggil for the Kraton; Siti Hinggil as "Central Symbolism" is also a symbol of the greatness of the king who has the duty as regulator and supervisor of the world in pre-NKRI period. This research would like to see the current function and change management of North Siti Hinggil Kasunanan Palace Surakarta. This research will use some cultural and economic theories in the analysis and use qualitative methodology in collecting and analyzing data. Siti Hinggil originally used for legitimacy purposes in the coronation ceremony of the king and as a space to show the authority and power of the king. The influence of the opening of Siti Hinggil as a public space (factual & virtual space) was felt by the Kraton Society, Public Society, and Government both Regional and Central. Consequently, the Kraton which was originally considered very exclusive, can be known by the public society, the art community, the intellectual community, and tourists. In contrast, Kraton can introduce itself to all layers of society as a source of Javanese culture through cultural products that until now enjoyed, imitated and used by the people of Central Java in particular.Keywords: Siti Hinggil Kasunanan Palace Surakarta, Function, Management, Tourism